Main directions of language policy of the Republic of the Kazakhstan - Amanbayeva, G.Yu.; Issabek, Sh.N. (KSU Publ., 2017)
Language, being one of the main characteristics of society, performs communicative function. On the frequency of the use of language on what volume language is de jure allocated with this or that official status, and de facto occasionally has no legitimate rights, it is possible to describe the considered society. The author has devoted the present article to one of the topical issues of modern independent Kazakhstan - language policy. Considering the main features of language policy in the Republic of Kazakhstan, the author plans the main directions, problems, the positive and negative moments. Such concepts as language policy, a language situation, bilingualism, a multilingualism are considered. The review of researches devoted to language policy of Kazakhstan is made.
Қазақстан Республикасы тіл саясатының негізгі бағыттары
Основные направления языковой политики Республики Казахстан
Keywords: language policy; language situation; education; education; native language; development; status; bilingualism; multilingualism